Psychological Impact of COVID-19 on Healthcare Workers: A Systematic Review - Victor Trismanjaya Hulu; Suharni Pintamas Sinaga; Achmad Rifai; Frans Judea Samosir; Putranto Manalu (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
During the COVID-19 pandemic, many health workers working in hospitals experienced psychological problems and stress while serving patients because of their high risk of contracting COVID-19. This study explores the main findings from the literature examining the psychological impact of COVID-19 on healthcare workers. This study uses a systematic review method using the PRISMA statement. A systematic search was carried out to obtain relevant articles from three databases, namely Scopus, PubMed, and Google Scholar, published in the English version. The investigation of articles started from identifying, sorting, checking the feasibility and eligibility of the studies and including qualitative synthesis. This article's inclusion criteria were English-language articles and full text on studies assessing the psychological impact of COVID-19 on healthcare workers. There were 1429 articles found and eleven studies of which were analyzed, namely ten studies using a cross-sectional design, one study using a retrospective cohort design. The psychological impact experienced by health workers included fear of being infected with COVID-19; fear of contracting oneself, friends, and relatives; fear of being alienated by others; fear of being stigmatized by others; worrying about personal and family health; worrying about being quarantined or isolated; fear of close contact with patients at high risk of infection; fear of experiencing high insomnia; fear of experiencing acute stress disorders and psychological stress. The study concluded that health workers serving patients in hospitals face tasks full of pressure, worry, anxiety, and high fear of being infected with COVID-19. Health workers are in dire need of health protection as well as special recovery programs that aim to improve psychological well-being during the COVID-19 pandemic.  Abstrak: Selama masa pandemi COVID-19, banyak tenaga kesehatan yang bekerja di rumah sakit mengalami gangguan psikologis dan stres saat melayani pasien karena besar risiko mereka terinfeksi COVID-19. Penelitian ini bertujuan untuk mengeksplorasi temuan utama dari literatur yang meneliti tentang dampak psikologis COVID-19 pada petugas kesehatan. Penelitian ini menggunakan metode systematic review dengan menggunakan pernyataan PRISMA. Untuk memperoleh artikel yang relevan maka dilakukan pencarian secara sistematis dari tiga database yaitu Scopus, PubMed dan Google Scholar yang diterbitkan dalam versi bahasa Inggris. Penyelidikan artikel dimulai dari tahap identifikasi, pemilahan, kelayakan dan studi yang memenuhi syarat dan termasuk sintesis kualitatif. Kriteria inklusi adalah artikel berbahasa Inggris dan full text tentang studi yang menilai dampak psikologis COVID-19 pada petugas kesehatan. Dari tiga database diperoleh 1429 artikel dan sebanyak 11 (sebelas) studi diantaranya dianalisis dimana sepuluh studi yang menggunakan desain cross-sectional dan satu studi yang menggunakan desain kohort retrospektif. Dampak psikologis yang dialami oleh tenaga kesehatan meliputi takut terinfeksi COVID-19, takut tertular terhadap diri sendiri, teman dan kerabat, takut dijauhkan oleh orang lain, takut distigmatisasi oleh orang lain, khawatir tentang kesehatan pribadi dan keluarga, khawatir akan dikarantina atau diisolasi, takut kontak dekat dengan pasien berisiko tinggi terinfeksi, takut mengalami insomnia yang tinggi, takut mengalami gangguan stres akut dan tekanan psikologis. Penelitian menyimpulkan petugas kesehatan yang melayani pasien di rumah sakit selalu diperhadapkan dengan pekerjaan yang penuh dengan tekanan, khawatir, cemas dan rasa takut yang tinggi terinfeksi COVID-19. Petugas kesehatan sangat membutuhkan perlindungan kesehatan serta program khusus pemulihan yang bertujuan untuk meningkatkan kesejahteraan psikologis selama pandemi COVID-19.